The continuance of gender culture amid change in Mexican-American immigrant Catholic contexts - Hooge Michalka, Karen (Journal of contemporary religion, 2019)
The acceptance and implementation of Roman Catholic teachings on marriage, sexuality, and the family vary both at the individual and at the parish level. While overall, there is a dialectical relationship between gender and religion in the way they inform and mold each other, the majority of research has focused on how religion has shaped gender in communities. We use qualitative data from a Latino immigrant Catholic context in the United States to show the opposite movement: how a Mexican-American gender culture of machismo and marianismo shapes the religious culture in the arenas of marriage and religious authority. The process of incorporating immigrant Mexicans into the dominant culture of the United States takes place in part in these religious centers through the interaction and mixture of Latino gender norms with the therapeutic egalitarianism of the white middle class, through the mediation of priests. Through this, we suggest that there are contexts, times, and places where the gender culture of a community shapes the reception and practice of religion.